Limit cycles of cubic polynomial differential systems with rational first integrals of degree 2 - Llibre, Jaume; Lopes, Bruno D. [UNESP]; Moraes, Jaime R. de [UNESP] (Elsevier B.V., 2015)
The main goal of this paper is to study the maximum number of limit cycles that bifurcate from the period annulus of the cubic centers that have a rational first integral of degree 2 when they are perturbed inside the class of all cubic polynomial differential systems using the averaging theory. The computations of this work have been made with Mathematica and Maple. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Polynomial vector fields; Limit cycles; Isochronous centers; Periodic orbits; Averaging method